2D Hydrogen-bonded polymer assembled by zinc(II) tetraaza macrocyclic complex and 1,2-cyclopentanedicarboxylic acid - Choi Ki-Young (Main Group Metal Chemistry, 2014)
The self-assembly of [Zn(L)(H2O)2]·Cl2 and 1,2-cyclopentanedicarboxylic acid generates a 2D hydrogen-bonded polymer [Zn(L)(Hcpdc)] (L=3,14-dimethyl-2,6,13,17-tetraazatricyclo[14,4,01.1807.12]docosane, H2 cpdc= 1,2-cyclopentanedicarboxylic acid) (1). Complex 1 is characterized by X-ray crystallography, spectroscopy, and thermogravimetric analyzer. The crystal structure of 1 shows a distorted octahedral coordination geometry around the zinc (II) ion, with the four secondary amines of the macrocycle and two carboxylate oxygen atoms of the Hcpdc- ligand in the trans position. The compound crystallizes in the monoclinic system P21/c with a=8.6002(10), b=10.4906(11), c=19.008(2) Å, β (°)=92.949(7)°, V=1712.6(3) Å3, Z=2. The IR spectrum and TGA behavior of the compound are significantly affected by the Hcpdc- ligand.